2015
DOI: 10.3329/bjar.v40i1.23760
|View full text |Cite
|
Sign up to set email alerts
|

Green cob and fodder yield of sweet corn as influenced by sowing time in the hilly region

Abstract: A field experiment was conducted at the farm of Hill Tract Agricultural Research Station, Ramgarh, Khagrachari Hill District during Rabi season of 2010-11 and 2011-12 to determine the optimum sowing time for better yield of green cob as well as fodder of sweet corn (var. BARI Sweet corn-1) in the hilly region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…2). Delayed planting had adverse effect on leaf area resulting in lower total dry matter and ultimately reduced yield (Shaheenuzzamn et al, 2015). Reduced leaf growth resulted in smaller canopy and produce smaller tuber.…”
Section: Resultsmentioning
confidence: 99%
“…2). Delayed planting had adverse effect on leaf area resulting in lower total dry matter and ultimately reduced yield (Shaheenuzzamn et al, 2015). Reduced leaf growth resulted in smaller canopy and produce smaller tuber.…”
Section: Resultsmentioning
confidence: 99%
“…Lower values for cob diameter and cob fresh mass under water stress conditions was reported (Parizi et al, 2009). These variables are strong yield indicators in corn crops because, the greater the corn mass, the greater the grain mass is (Shaheenuzzamn et al, 2015). This may also explain, in part, the significant differences for cob diameter and fresh weight as productivity spiked with the different soil water tensions.…”
Section: Discussionmentioning
confidence: 90%
“…Their report indicated that the cob length ranged between 19.1 and 20.4, and 17.7 and 21.8 in cultivars and sowing dates, respectively. Shaheenuzzamn et al (2015) reported that sowing date significantly affected the cob length and diameter. Also reported that cob diameter changed between 4.09 cm and 4.44 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, argue that when sowing date was delayed, sweet corn yield decreased. In addition, early sowings were suggested for successful sweet corn production in the hilly areas (Shaheenuzzamn et al, 2015). Therefore, in order to make the best use of soil moisture, plant nutrients, and solar radiation and to obtain a high-quality yield, optimum sowing date should be determined (Keerthi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%